Federalism comparative perspectives from India and Australia - Copland,Ian; Copland, Ian 1943; Rickard, John 1935; Monash University. National Centre for Australian Studies; Monash University. Centre of South Asian Studies (Manohar Publishers & Distributors New Delhi, 1999)
Seminar papers.
"Published in association with the National Centre for Australian Studies and the Centre of South Asian Studies, Monash University, Melbourne."
Includes bibliographical references and index.
Keywords: Federal government -- Congresses. -- India; Decentralization in government -- Congresses. -- India; Intergovernmental fiscal relations -- Congresses. -- India; Federal government -- Congresses. -- Australia; Decentralization in government -- Congresses. -- Australia; Intergovernmental fiscal relations -- Congresses. -- Australia